Technological Pride and National Resilience: How Innovation Shapes Stability and Security - Sarjito, Aris (Lembaga Ketahanan Nasional Republik Indonesia, 2024)
Purpose: This study examines how technological innovation influences national resilience, stability, and security in Indonesia. It focuses on cybersecurity, digital infrastructure, and renewable energy as key factors in strengthening national unity and mitigating internal and external threats. The study also explores how technological pride fosters social cohesion and enhances Indonesia’s role as a regional technology leader in ASEAN. Design/Methodology/Approach: A qualitative research approach is used, analyzing secondary data from government reports, policy documents, academic literature, and media sources. Thematic analysis identifies patterns in technological innovation, national security, and public confidence. A case study approach examines Indonesia’s cybersecurity strategies, digital transformation policies, and renewable energy initiatives. Triangulation is applied to ensure data validity and reliability. Findings: Findings show that technological pride strengthens public confidence, particularly in times of crisis, such as the COVID-19 pandemic. Investment in digital infrastructure and cybersecurity enhances national security by reducing cyber threats. Progress in renewable energy supports energy independence, reducing reliance on fossil fuels. Indonesia’s technological leadership in ASEAN also fosters regional security cooperation, particularly in cybersecurity and energy security. Originality/Value: This study provides a comprehensive perspective on the intersection of technological advancement, national resilience, and security, an area that remains underexplored in Indonesia. Unlike previous studies focusing on cybersecurity or energy separately, this research links these aspects to national stability and geopolitical influence. The findings offer practical insights for policymakers and security agencies, emphasizing the need for sustained investment in innovation, digital literacy, and strategic collaboration to maintain Indonesia’s long-term technological resilience and security.